DIGITAL PEDAGOGY IN HIGHER EDUCATION: OPPORTUNITIES AND CHALLENGES (World Bulletin of Social Sciences, 2026)
This paper explores digital pedagogy, the role of e-learning technologies and Virtual Learning Environments (VLEs) in contemporary higher education. It examines how Learning Management Systems, video-conferencing platforms, and AI-supported tools have reshaped teaching practices and improved student-centered learning experiences. The study outlines the conceptual foundations of digital pedagogy, emphasizing learner autonomy, active engagement, flexibility, personalization, and the development of digital literacy. Particular attention is given to the pedagogical potential of VLEs as integrated ecosystems that support collaboration, assessment, and feedback beyond the physical classroom. At the same time, the paper highlights critical challenges related to the digital divide, student engagement, academic integrity, data privacy, and educators’ digital competence. The analysis demonstrates that technology alone does not guarantee effective learning outcomes; instead, meaningful educational impact depends on theoryinformed curriculum design and purposeful instructional strategies. The paper concludes that when thoughtfully implemented, digital pedagogy can contribute to more equitable, effective, and human-centered learning experiences.
Keywords: Digital pedagogy; e-learning technologies; virtual learning environments